The influence of ceramic admixture on physical and chemical properties of surgical cement - Balin, A.; Myalski, J.; Pucka, G.; Toborek, J. (Polimery, 2022)
The results of modification of two commercial grades of poly(methyl methacrylate) based surgical cements, widely used in clinical practice, focused on lowering of its linear contraction and polymerization temperature (Fig. 1) were presented. The effects of admixtures: Al2O3 of various granulations and glassy like coal, introduced into the cements, on the changes of these parameters (Fig. 2-6) were evaluated. Mechanical properties of cements admixed, namely compressive strength (Rc), flexural strength (Rg) and moduli of elasticity (Ec, Eg, Er) (Fig. 7-10) were determined as well. Because of fatigue character of the interactions during the cement use for fixing of joint endoprostheses, the strength features of the materials were evaluated using low-cycle fatigue method, leading to durability (Nf) determination (Fig. 11). It was found that ceramic admixtures decreased both the linear contraction of the cement samples and maximal polymerization temperature. Modification of a cement with glassy like coal gave the best set of the properties evaluated.